Toward Trans Reproductive Justice: A Qualitative Analysis of Views on Fertility Preservation for Australian Transgender and Non‐binary People. (18th December 2019) - Riggs, Damien W.; Bartholomaeus, Clare
Abstract: This article draws on three Australian studies focused on views about fertility preservation among (1) parents of transgender and non‐binary children, (2) transgender and non‐binary adults, and (3) healthcare professionals working with transgender and non‐binary people. The first two studies were undertaken concurrently given the dearth of research on the topic in the Australian context, and the third study was then undertaken given a primary focus on healthcare professionals in responses to the first two studies. For the present article, a deductive thematic analysis framed by a reproductive justice lens was undertaken on qualitative data from each study. Findings from the first study suggest that while some parents may be supportive of their child's reproductive wishes, other parents may insist upon their child undertaking fertility preservation. In the second study, transgender and non‐binary adults emphasized that gamete retrieval may be framed in cisgenderist ways by healthcare professionals, and that professionals may endorse pronatalism. Finally, healthcare professionals reported normative views about gamete retrieval and framed fertility preservation as an "insurance policy." This article concludes by considering what the findings have to suggest for the continued development of trans reproductive justice.